Fallopian tube secretory cell expansion: a sensitive biomarker for ovarian serous carcinogenesis - Wang, Yiying (Am J Transl Res, 2016)
Recent advances suggest that precancerous lesions of pelvic serous carcinoma originate from tubal secretory cells. The purpose of our study was to determine if an increased number of secretory cells vary with age or location in the fallopian tube and to examine its association with serous neoplasia. Three groups (benign control, high-risk, and pelvic serous carcinoma) of age-matched patients were studied. The age data were stratified into 10-year intervals ranging from 20-29 to older than 80. The number of secretory and ciliated cells from both tubal fimbria and ampulla segments was counted by microscopy and immunohistochemical staining methods. The data were analyzed by standard contingency table and Poisson distribution methods after age justification. We found that the absolute number of tubal secretory cells increased significantly with age in all three groups. But a more dramatic increase of secretory cells was observed in high-risk and pelvic serous carcinoma patients. Secretory cell expansion is more prevalent than secretory cell outgrowth in both fimbria and ampulla tubal segments and is significantly associated with serous neoplasia (p < 0.001). Furthermore, age remained a significant risk factor for serous neoplasia after age adjustment. These findings suggest that secretory cell expansion could serve as a potential sensitive biomarker for early serous carcinogenesis within the fallopian tube. The study also supports a relationship between serous neoplasia and increased secretory to ciliated cell ratios, and the relationship between frequency of secretory cell expansion within the fallopian tube and increasing age and-more significantly-presence of high-risk factors or co-existing serous cancers.